Zirconium nanoparticles based solid phase extraction-slotted quartz tube-flame atomic absorption spectrophotometry for the determination of cadmium in wastewater samples and evaluation of green profile - Tekin, Zeynep; Ozdogan, Nizamettin; Bakirdere, Sezgin (TAYLOR & FRANCIS LTD, 2022)
In this paper, a novel zirconium nanoparticles (Zr-NPs)-based solid-phase extraction (SPE) strategy was established for the accurate and sensitive determination of cadmium at trace levels prior to slotted quartz tube-flame atomic absorption spectrophotometry (SQT-FAAS) system. Zr-NPs were synthesised with a simple and fast method and utilised as adsorbents for the extraction of the analyte from aqueous samples. The primary factors affecting the extraction recovery such as nanoparticle amount, mixing type and period, type and volume of eluent were optimised by single variant experiments to obtain optimal extraction conditions. Under the optimised conditions, the calibration plot of the method showed a linear range of 2.0-25 mu g L-1 with a regression coefficient of 0.9993. The limit of detection and limit of quantification obtained were 0.44 and 1.46 mu g L-1, respectively. In order to make sure whether the developed method is applicable to complex matrices, an extraction procedure was successfully applied to wastewater samples. For this purpose, spiked recovery studies were performed at three different cadmium concentration. The per cent recoveries were obtained between 96.1% and 100.7% with low per cent relative standard deviations. Thus, the proposed method was validated and confirmed its high accuracy and precision with satisfactory recoveries.
Keywords: Cadmium; zirconium nanoparticles; flame atomic absorption spectrophotometer; solid-phase extraction; wastewater; ONLINE PRECONCENTRATION; TRACE CADMIUM; MICROEXTRACTION; SPECTROMETRY; REMOVAL; SYSTEM; COPPER; LEAD; Chemistry; Environmental Sciences & Ecology